Decomposition Analysis of Household Electricity Consumption in South Korean Municipalities - Sung, Yeolhoon; Lee, Jooyeoun; Chung, Myoungsug (Proceedings of the IEEE International Conference on Big Data and Smart Computing, BIGCOMP, 2025)
This study analyzes the drivers of residential electricity consumption growth in seven major cities in South Korea - Seoul, Busan, Daegu, Incheon, Gwangju, Daejeon, and Ulsan - over the period from 2002 to 2022. The analysis applies the Logarithmic Mean Divisia Index (LMDI) methodology to evaluate the contributions of factors disaggregated into the number of households, income per household, energy intensity, electrification rate, and climate effects. The results reveal that increases in the number of households and income per household were the primary drivers of electricity consumption growth, whereas reductions in energy intensity contributed to mitigating consumption. In most cities, income per household emerged as the dominant driver of increased electricity consumption. However, in Ulsan, the rise in the electrification rate was identified as the most significant contributing factor. The influence of climate change was relatively minor. This study provides a foundation for formulating regional policies by identifying the drivers of residential electricity consumption in each city.
Keywords: Decomposition analysis; Divisia index; Electricity-consumption; Electrification rate; Energy intensity; Index analysis; Logarithmic mean; Logarithmic mean divisia index analyze; Net-zero; Residential electricity consumption; climate change; electricity consumption; electrification rate; energy intensity; LMDI analysis; Net-zero